Challenges in the provision of community aged care in China. Issue 2 (1st June 2013) - Yang, Hui; Browning, Colette; Thomas, Shane
Abstract : Objective: Population ageing in China is a significant challenge for the Chinese government, the society and Chinese people. The dramatic process of population ageing together with social and economic diversity in China has created issues in the availability, equality and sustainability of social and financial support for older people. The aims of this review are to identify the social and economic challenges to the traditional caregiving system in China, and to examine possible solutions to improve the care of older people in China using the framework of ageing in place. Methods: Electronic literature searches were conducted in May and June 2013 using PubMed, CNKI, and MEDLINE. Statistical data and reports were retrieved from the United Nations, the World Health Organisation, the World Bank and National Bureau of Statistics of China. Government policy documents were found through government websites and formal publications. Results: Family-centred care for older people in China is recognised as a cultural tradition in the Chinese community. However, driven by large-scale social, political and economic changes, this model of caring for older people has dynamically changed over the last 50 years. Traditionally the family has been the most important source of social support for older people followed by neighbour support and support from friends. Today family obligations of caring are still centred in a cultural and practical context; however, support from family and children has weakened incrementally. Community-based aged services are absent in most areas, while older people and their families have to pay out-of-pocket expenses for non-residential services. There is a severe shortage of aged care or nursing home resources in China and those that exist are of low quality and expensive. The staff who work in these facilities rarely have any formal training in aged care. In addition, a market approach to the funding of residential aged care has the potential to create a moral hazard due to the poor regulatory control of aged care in China. While the building of residential aged care homes is seen as the solution to the care of older people in China, older people prefer to age in their own homes and expect the restoration of the family care tradition as well as more government support for them to "age in place". This approach has the potential to be more cost effective than expensive aged care facilities. Conclusion: Given older people's preferences, ageing in place, with the provision of community services and family support, potentially provides a fair and financially viable approach to promote healthy ageing and supportive care in China. Further studies are required to identify 1) how ageing in place can be supported by a national strategy, 2) the financial arrangements required to fund such an approach, and 3) how to train high quality community-based professionals in both rural and urban areas to support the care of older people.